2D map projections for visualization and quantitative analysis of 3D fluorescence micrographs - Sendra, Hernán Gonzalo; Hoerth, Christian; Wunder, Christian; Lorenz, Holger (Scientific reports, 2015)
We introduce Map3-2D, a freely available software to accurately project up to five-dimensional (5D) fluorescence microscopy image data onto full-content 2D maps. Similar to the Earth’s projection onto cartographic maps, Map3-2D unfolds surface information from a stack of images onto a single, structurally connected map. We demonstrate its applicability for visualization and quantitative analyses of spherical and uneven surfaces in fixed and dynamic live samples by using mammalian and yeast cells and giant unilamellar vesicles. Map3-2D software is available at http://www.zmbh.uni-heidelberg.de//Central_Services/Imaging_Facility/Map3-2D.html.
Gesehen am 16.06.2020